MANAJEMEN WAKTU DAN KOMPETENSI PROFESIONAL GURU TAMAN KANAK-KANAK DALAM PENYELENGGARAAN KEGIATAN PEMBELAJARAN DI TK GUGUS I- XVII KECAMATAN SAWAHAN KOTA SURABAYA - Furta Desi Heris Sundy; Chamariyah Chamariyah; Ruddy Wiroko (Jurnal Manajerial Bisnis, 2018)
This study aims to improve the competence of professionalism of teachers to support the progress and improvement of the quality of learning and improve learning outcomes and at the same time to improve the quality of education. Type of research used in this research is descriptive research, research approach used is qualitative approach. As the object of this research is Kindergarten Types I-XVII Sawahan District Surabaya City. Based on the results of interviews with research informants, it can be seen the constraints faced by schools in general are the limited infrastructure in the form of books and learning media in supporting teaching and learning activities in schools, although the constraints do not occur in all schools. Then the supporting factor is the availability of facilities such as classroom, school playground for children, teachers' ability to communicate and experience of the teacher to be one cover of the shortcomings or constraints faced by each school.